May I Smell Your Attention: Exploration of Smell and Sound for Visuospatial Attention in Virtual Reality - Dozio, Nicolò; Maggioni, Emanuela; Pittera, Dario; Gallace, Alberto; Obrist, Marianna (Frontiers in Psychology, 2021)
When interacting with technology, our attention is mainly driven by audio-visual and increasingly haptic stimulation. Olfactory stimuli are widely neglected, although our sense of smell influences many of our daily life choices, affects our behavior, and can catch and direct our attention. In this paper, we investigated the effect of smell and sound on visuospatial attention in a virtual environment. We implemented the Bells Test, an established neuropsychological test to assess attentional and visuospatial disorders, in Virtual Reality (VR). We conducted an experiment with 24 participants comparing users’ performance in three experimental conditions (smell, sound, smell and sound). Our results show that multisensory stimuli play a key role in driving participants’ attention and highlight asymmetries in directing spatial attention. We discuss the relevance of our results within and beyond Human-Computer Interaction (HCI), particularly with regards to the opportunity of using VR for rehabilitation and assessment procedures for patients with spatial attention deficits.